Modifying the farmer field school method to support on-farm adaptation of complex rice systems. Issue 3 (27th May 2019) - Khumairoh, Uma; Lantinga, Egbert A.; Suprayogo, Didik; Schulte, Rogier P. O.; Groot, Jeroen C. J.
ABSTRACT: Purpose: Complex rice systems (CRSs) are polycultures of plants and animals that enhance ecological processes contributing to sustainable and profitable farming systems. However, the contextual management complexity can hamper adoption, despite the large long-term benefits that CRSs offer. This paper aimed to provide a method that encourages active farmer involvement and integrates farmer's feedback to deliver timely adaptations to CRS management. Design/methodology/approach: FFSs that are commonly used in guiding rural development processes involve a long process of preparation, weekly meetings and dissemination of new technologies with a greater knowledge flows from researchers or institutions to farmers than contrariwise. We have simplified FFS components and modified its curriculum focusing on extracting and integrating farmers' feedback into adaptation measures. Surveys were conducted and their results were validated through focus group discussions, which provided an adequate database to simplify the steps in the FFS approach. Findings: Only four meetings for agroecosystems analysis that emphasised an analytical and reflective learning cycle generated suitable adaptation measures selected from farmers' feedback. Repetition of the shortened FFS over several rice cropping cycles proved more effective than the frequent meetings within one cropping cycle. Practical implications: The modified FFS could be considered as a promising approach to training farmers, whilst simultaneously identifying and discovering adaptations of agricultural innovations and monitoring the evolution of complex polycultures like CRSs, under diverse conditions. Theoretical implications: The modified FFS provides participants additional time to reflect on the training topics, resulting in a significant improvement in their knowledge and the performance of the CRS. Originality/value: The modified FFS approach is focused on reflexive learning cycles and adaptation of innovations. Therefore, it is highly suitable for management of complex polycultures such as CRSs.